Differential recombination dynamics within the MHC of macaque species - de Groot, Nanine (Springer Berlin Heidelberg, 2014)
A panel of 15 carefully selected microsatellites (short tandem repeats, STRs) has allowed us to study segregation and haplotype stability in various macaque species. The STRs span the major histocompatibility complex (MHC) region and map in more detail from the centromeric part of the Mhc-A to the DR region. Two large panels of Indian rhesus and Indonesian/Indochinese cynomolgus macaques have been subjected to pedigree analysis, allowing the definition of 161 and 36 different haplotypes and the physical mapping of 10 and 5 recombination sites, respectively. Although most recombination sites within the studied section of the Indian rhesus monkey MHC are situated between the Mhc-A and Mhc-B regions, the resulting recombination rate for this genomic segment is low and similar to that in humans. In contrast, in Indonesian/Indochinese macaques, two recombination sites, which appear to be absent in rhesus macaques, map between the class III and II regions. As a result, the mean recombination frequency of the core MHC, Mhc-A to class II, is higher in Indonesian/Indochinese cynomolgus than in Indian rhesus macaques, but as such is comparable to that in humans. The present communication demonstrates that the dynamics of recombination ‘hot/cold spots’ in the MHC, as well as their frequencies, may differ substantially between highly related macaque species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00251-014-0783-4) contains supplementary material, which is available to authorized users.